SOCIAL COMPARISON PHENOMENON ON SOCIAL MEDIA AND EMOTIONAL INSTABILITY - Ostanakulov Alijon Dadajon ugli; Tojimamatov Jamshidbek Iqboljon ugli (Bright Mind Publishing, 2026)
This article examines the phenomenon of social comparison on social media and its impact on emotional instability from a psychological perspective. In the context of digital communication, mechanisms of self-evaluation and identity construction have undergone significant transformation. Social media platforms intensify upward and downward comparison processes, influencing affective reactivity, anxiety, depressive symptoms, and self-esteem. The study integrates theoretical analysis with empirical data obtained from young adult participants to explore the relationship between social comparison tendencies and emotional instability indicators. The findings suggest that upward comparison is significantly associated with higher levels of anxiety, dissatisfaction, and affective volatility, while downward comparison provides only temporary emotional compensation. Preventive and corrective psychological implications are discussed.
Keywords: Social comparison, emotional instability, affective reactivity, social media, self-esteem, upward comparison, downward comparison, digital identity, psychological well-being, media literacy.